STRATEGIC INTERNATIONALIZATION STARTS AT HOME: THE CASE OF CAPACITY CREATION IN THE DEMOCRATIC REPUBLIC OF CONGO (DRC) - Richard Lobron (Journal of International Conference Proceedings (JICP), 2018)
The 2016 outbursts of nationalism in Europe and in the US have left globalization moribund. Investing domestically is becoming a strategy to remain competitive globally. We wonder how the creation of capacity for transportation infrastructure, leveraging internationalization, affects economic development. We nurture our reflections through the field observations of a US expert whose expertise was requested by DRC leaders. Our inductive approach is rigorously based on the case study methodology. We find that the lack of capacity to perform infrastructure development can be addressed by Western and local institutions, generating relationships that can lead to greater internationalization. This paper explores the needs of programs and methods through which Western Universities and local organizations can provide such capacity, even in one of the most challenging business environments on Earth. While our research cannot be generalized, it is applicable to organizations that seek to remain competitive domestically by capitalizing on internationalization. Keywords: Africa, internationalization, professional capacity, workforce development, project management, strategy.